IL-21 Promotes CD4 T Cell Responses by Phosphatidylinositol 3-Kinase–Dependent Upregulation of CD86 on B Cells - Attridge, Kesley (AAI, 2014)
The cytokine IL-21 is a potent immune modulator with diverse mechanisms of action on multiple cell types. IL-21 is in clinical use to promote tumor rejection and is an emerging target for neutralization in the setting of autoimmunity. Despite its clinical potential, the biological actions of IL-21 are not yet fully understood and the full range of effects of this pleiotropic cytokine are still being uncovered. In this study, we identify a novel role for IL-21 as an inducer of the costimulatory ligand CD86 on B lymphocytes. CD86 provides critical signals through T cell–expressed CD28 that promote T cell activation in response to Ag engagement. Expression levels of CD86 are tightly regulated in vivo, being actively decreased by regulatory T cells and increased in response to pathogen-derived signals. In this study, we demonstrate that IL-21 can trigger potent and sustained CD86 upregulation through a STAT3 and PI3K-dependent mechanism. We show that elevated CD86 expression has functional consequences for the magnitude of CD4 T cell responses both in vitro and in vivo. These data pinpoint CD86 upregulation as an additional mechanism by which IL-21 can elicit immunomodulatory effects.